2019
DOI: 10.3390/fermentation5040086
|View full text |Cite
|
Sign up to set email alerts
|

The Biodiversity of Saccharomyces cerevisiae in Spontaneous Wine Fermentation: The Occurrence and Persistence of Winery-Strains

Abstract: Saccharomyces cerevisiae populations occurring in spontaneous wine fermentations display a high polymorphism, although few strains are generally able to dominate the fermentative process. Recent studies have suggested that these indigenous S. cerevisiae strains are representative of a specific oenological ecosystem, being associated to a given wine-producing area or a single winery. In contrast, according to other ecological studies, no correlation between genotypic and phenotypic groups of the native S. cerev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
5
12
0
Order By: Relevance
“…Richness of S. cerevisiae found at the different stages of the winemaking process, mainly the differences found between the CM and RM stages, can be explained in accordance with previous studies which confirmed the influence of the air and winery environment in spontaneous fermentations. Thus, resident strains of S. cerevisiae at the winery may be well adapted and easily implanted compared to those from the grape [ 5 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Richness of S. cerevisiae found at the different stages of the winemaking process, mainly the differences found between the CM and RM stages, can be explained in accordance with previous studies which confirmed the influence of the air and winery environment in spontaneous fermentations. Thus, resident strains of S. cerevisiae at the winery may be well adapted and easily implanted compared to those from the grape [ 5 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Lene [Lene 2003], several isolates of S. cerevisiae were found to be involved in fermentation. S. cerevisiae shows the polymorphism with some isolates even show phenotypic as well as genotypic characters are different from normally recognized S. cerevisiae strains [Granchi et al, 2019].…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the presence of the dominant S . cerevisiae species is attributed to their adaptation capability to stressful environmental conditions, such as increasing ethanol concentrations and temperature changes during the fermentation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%